Antibiotic resistance pattern and biofilm formation among clinical Acinetobacter baumannii isolates: A cross-sectional study - Vahab Hassan Kaviar; Zahra Farshadzadeh; Azar Dokht Khosravi; Mohammad Hossein Haddadi; Somayeh Karamolahi; Marzieh Hashemian; Nazanin Omidi; Moloudsadat Motahar; Nourkhoda Sadeghifard; Saeed Khoshnood; Fatemeh Shahi (Journal of Acute Disease)
Objective: To investigate the pattern of antibiotic resistance and biofilm production capabilities of clinical Acinetobacter baumannii (A. baumannii) isolates in this study. Methods: A. baumannii isolates were collected from Tehran Imam Khomeini Hospital in this cross-sectional study, and the minimum inhibitory concentrations for 16 antibiotics were determined using Vitek2® systems. All isolates were analyzed for biofilm production, then presence of biofilm-associated genes, and class I and II integron genes. Results: 60 non-replicate A. baumannii isolates were included in this study. The resistance rates reached 100% for aztreonam, cefepime, ceftazidime, ciprofloxacin, piperacillin-tazobactam, piperacillin, ticarcillin, and trimethoprim-sulfamethoxazole. A. baumannii isolates were most sensitive to colistin and rifampicin being the most effective treatments. Multi-drug resistant and extensively drug-resistant isolates accounted for 83.3% and 16.7%, respectively. Of the isolates, 91.6% formed biofilms, categorized as 10% strong, 31.6% moderate, and 50% weak. No correlation was found between antibiotic resistance and biofilm formation. The genes csuE, abaI, and ompA were prevalent, but their distribution was similar across biofilm categories. A relationship between Int1 and biofilm production was noted. Conclusions: The high rates of antibiotic resistance and biofilm formation, alongside the presence of integrons including class I and II, underscore the necessity for ongoing monitoring of A. baumannii. Notably, class I integron presence was significantly linked to biofilm formation. Further research is needed to explore the connection between antibiotic resistance and biofilm production in A. baumannii.